2023
DOI: 10.2478/logi-2023-0001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Number of Required Charging Stations on a German Motorway Based on Real Traffic Data and Discrete Event-Based Simulation

Abstract: To make travelling with electric vehicles (EVs) over long distances as convenient as travelling with traditional vehicles, charging stations along motorways are necessary. Furthermore, waiting times for free charging points must be short to enable a fast onward journey, and this also on days with heavy traffic volumes. To determine the required number of charging stations in more detail, a model was created that simulates the process of arriving and leaving cars at a charging park based on real traffic data. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The use of railway power infrastructure to charge electric vehicles is not a frequently used solution. However, there are several technical solutions regarding charging, power supply and the intercorrelation of electric vehicles with electric traction networks (mainly with urban traction networks powering trams, metro and trolleybuses) [1,[12][13][14][18][19][20][21][22][23][24][25][26].…”
Section: Review Of Technical Solutions For Charging Electric Vehicles...mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of railway power infrastructure to charge electric vehicles is not a frequently used solution. However, there are several technical solutions regarding charging, power supply and the intercorrelation of electric vehicles with electric traction networks (mainly with urban traction networks powering trams, metro and trolleybuses) [1,[12][13][14][18][19][20][21][22][23][24][25][26].…”
Section: Review Of Technical Solutions For Charging Electric Vehicles...mentioning
confidence: 99%
“…The development of electromobility in the context of covering longer distances was dealt with by the author of publication [26]. The author developed a model simulating a journey, taking into account arrival and entry to the charging station based on real traffic data, to determine the required number of charging stations.…”
Section: Review Of Technical Solutions For Charging Electric Vehicles...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking a view on the contemporary research of the digitization of the work environment is necessary to keep health and safety in the digitized world. Digitization enables saving and processing data much better, they are more easily accessible and clearer with the help of algorithms [22]. Digitalization promises a marked increase in productivity for societies affected.…”
Section: Literature Review and Analysis Of The Current Statementioning
confidence: 99%
“…They also found that standing vehicles and at speeds below 15 th percentile speeds produce much higher CO 2 to the environment and the reason is attributed to intersections and SMVs. An increase in EVs and autonomous vehicles can decrease the proportions of SMVs like 3-wheelers, which impact the traffic flow, [35]. Therefore, it can be said that many researchers have directly or indirectly addressed the problems faced by SMVs on the road, but have not much assessed it as their objectives were different.…”
Section: Artificial Neural Networkmentioning
confidence: 99%